Kinetic parameters for nutrient enhanced crude oil biodegradation in intertidal marine sediments - Singh, Arvind K.; Sherry, Angela; Gray, Neil D.; Jones, D. Martin; Bowler, Bernard F. J.; Head, Ian M. (Frontiers in Microbiology, 2014)
Availability of inorganic nutrients, particularly N and P, is often a primary control on crude oil hydrocarbon degradation in marine systems. Nevertheless, there is a paucity of information on fundamental kinetic parameters for nutrient enhanced crude oil biodegradation that can be used to model the fate of crude oil in bioremediation programmes that use inorganic nutrient addition to stimulate oil biodegradation. Here we report fundamental kinetic parameters (Ks and qmax) for nitrate- and phosphate-stimulated crude oil biodegradation under nutrient limited conditions and with respect to crude oil, under conditions where N&P are not limiting. Crude oil degradation was limited by both N&P availability. When N was added alone maximum rates of CO2 production measured were 3.94±0.46 µmol CO2 /g wet sediment/day. However when the same levels of N were added in the presence of 0.5% P w/w of oil (1.6 μmol P/g wet sediment) maximum rates of measured CO2 production more than doubled (11.52±0.72 µmol CO2 /g wet sediment/day). Ks and qmax estimates for N (in the form of sodium nitrate) when P was not limiting were 1.57±0.56 µmol/g wet sediment and 10.57±0.63 µmol CO2 /g wet sediment/day respectively. The corresponding values for P were 80 nmol/g wet sediment and 8.76±1.15 µmol CO2 /g wet sediment/day. The qmax values with respect to N and P were not significantly different (P< 0.05). Analysis of bacterial 16S rRNA genes indicated that Alcanivorax spp. were selected in these marine sediments with increasing inorganic nutrient concentration, whereas Cycloclasticus spp. were more prevalent at lower inorganic nutrient concentrations. These data suggest that simple empirical estimates of the proportion of nutrients added relative to crude oil concentrations may not be sufficient to guarantee successful crude oil bioremediation in oxic beach sediments. The data we present also help define the maximum rates and hence timescales required for bioremediation of beach sediments.